Consideration the Relationship between Information Communications Technology and Economic Growth in Top 10 Economic - Hossein, Sadr Seyed Mohammad (International Journal of Sustainable Development & World Policy, 2012)
In this paper, we examine the relationship between information and communications technology (ICT) development and economic growth in top 10 economic, using panel cointegration, and panel-based error correction models from annual data covering the period of 1980 to 2010. The empirical results support of a short-run cointegration relationship after allowing for the heterogeneous country effect. The long-run relationship is estimated using a full-modified OLS. The evidence shows that short run causalities run from ICT to GDP and vice versa. This means that an increase in ICT directly affects economic growth and that economic growth also stimulates further ICT. The direction of causation between ICT and economic growth has significant policy implications.